Studi Fenomenologi Persepsi Lansia Dalam Mempersiapkan Diri Menghadapi Kematian - Pupita - Harapan; Febriana - Sabrian; Wasisto - Utomo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
This research is qualitative study with descriptive phenomenology approach. The purpose is to describe various perception of elderly about preparation for death. Four participants were selected by purposive sampling method and used theory of saturation. Data were collected by in-depth interview which completed by field note and analyzed by Colaizzi method. This research identified five themes: self-concept, perception of death, factors influencing perception of death, preparation for death, and the processes of wishes for death. This research recommends that palliative care providers should understand that elderly patients’ perception of death and let them make decisions. It is important to provide the elders with religious activities as elders preparation for death. Keywords: elderly, perception, preparation for death References: 47 (1999-2013)